Drosophila Free-Flight Odor Tracking is Altered in a Sex-Specific Manner By Preimaginal Sensory Exposure. - Tolassy, V.; Cazalé-Debat, L.; Houot, B.; Reynaud, R.; Heydel, J.M.; Ferveur, J.F.; Everaerts, C. (Journal of Chemical Ecology, 2023)
In insects such as Drosophila melanogaster, flight guidance is based on converging sensory information provided by several modalities, including chemoperception. Drosophila flies are particularly attracted by complex odors constituting volatile molecules from yeast, pheromones and microbe-metabolized food. Based on a recent study revealing that adult male courtship behavior can be affected by early preimaginal exposure to maternally transmitted egg factors, we wondered whether a similar exposure could affect free-flight odor tracking in flies of both sexes. Our main experiment consisted of testing flies differently conditioned during preimaginal development in a wind tunnel. Each fly was presented with a dual choice of food labeled by groups of each sex of D. melanogaster or D. simulans flies. The combined effect of food with the cis-vaccenyl acetate pheromone (cVA), which is involved in aggregation behavior, was also measured. Moreover, we used the headspace method to determine the "odorant" identity of the different labeled foods tested. We also measured the antennal electrophysiological response to cVA in females and males resulting from the different preimaginal conditioning procedures. Our data indicate that flies differentially modulated their flight response (take off, flight duration, food landing and preference) according to sex, conditioning and food choice. Our headspace analysis revealed that many food-derived volatile molecules diverged between sexes and species. Antennal responses to cVA showed clear sex-specific variation for conditioned flies but not for control flies. In summary, our study indicates that preimaginal conditioning can affect Drosophila free flight behavior in a sex-specific manner.